1976
DOI: 10.1128/jb.127.1.461-468.1976
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural visualization of anionic sites on mycoplasma membranes by polycationic ferritin

Abstract: Anionic sites on mycoplasma membranes were visualized in the electron microscope by a polycationized ferritin derivative. The technique of thin sectioning was used. Staining prior to fixation led to clustering of ferritin granules on the mycoplasma cell surface. On glutaraldehyde-fixed Mycoplasma mycoides subsp. capri, M. gallisepticum, M. pneumoniae, and Acholeplasma laidlawii, the anionic sites were uniformly distributed over the entire membrane surface. M. hominis did not bind the polycationic ferritin labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The external location of at least some of the mycoplasma membrane phospholipids has been suggested by electron microscopy with ferric oxide hydrosols in propanoic acid (284) or polycationic ferritin (283) that bind to negatively charged groups on the membrane surface. The anionic sites appear to be lipid phosphate groups rather than protein carboxyls, since extraction of the membranes with lipid solvents abolished labeling, whereas Pronase treatment increased labeling (283,284). Striking membrane asymmetry was detected on labeling of isolated membranes of M. mycoides subsp.…”
Section: Membrane Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The external location of at least some of the mycoplasma membrane phospholipids has been suggested by electron microscopy with ferric oxide hydrosols in propanoic acid (284) or polycationic ferritin (283) that bind to negatively charged groups on the membrane surface. The anionic sites appear to be lipid phosphate groups rather than protein carboxyls, since extraction of the membranes with lipid solvents abolished labeling, whereas Pronase treatment increased labeling (283,284). Striking membrane asymmetry was detected on labeling of isolated membranes of M. mycoides subsp.…”
Section: Membrane Lipidsmentioning
confidence: 99%
“…The probe was found to bind to one membrane surface only, prewsmably the outer one (283). On the other hand, M. hominis membranes, even when isolated from cells, failed to react with the iron-containing labels unless membrane protein was first digested by Pronase (283). This is in accordance with previous findings showing that the major phospholipid of the M. hominis membrane, phosphatidylglyceroL resists hydrolysis by phospholipase C (266) and fails to interact with its specific antiserum (280) unless the membranes are first treated with Pronase, suggesting that membrane phospholipids in M. hominis are masked by proteins on both membrane sides.…”
Section: Membrane Lipidsmentioning
confidence: 99%
“…It is possible that interaction between A. laidlawii cells and liposomes occur as a result of a combination of hydrogen bonding and electrostatic forces. Schiefer et al (1976) showed that the net negative charge on the surface of Acholeplasma cells and that anionic sites were uniformly distributed over the entire membrane surface, although PC is a zwitterion (i.e. carries both positive and negative charges), the positive charge carried in the choline moiety will be on the surface of the molecule, thus making electrostatic adherence between acholeplasma cells and liposomes possible.…”
Section: Discussionmentioning
confidence: 99%
“…Using polycationic ferritin or positively charged ferric oxide hydrosols in propionic acid as probes, we have demonstrated by electron microscopy a dense and rather homogeneous layer of anionic binding sites on the membrane surface of A. laidlawii. With chemical and enzymatic techniques, the anionic sites were identified to be mainly lipid phosphate groups of, e.g., phosphatidylglycerol (32,33).…”
Section: Effect Of Gps On Viability Of a Laidlawiimentioning
confidence: 99%